The complex formation mechanism between β-cyclodextrin and organic micropollutants in water, studied by molecular dynamics simulations - De Vince, Oscar; Duan, Zhewen; Yang, Zhugen; Chevolot, Yann; Yeromonahos, Christelle (American Chemical Society (ACS), 2026)
Cyclodextrins are cage molecules with a hydrophilic exterior that promotes their solubility in water, while their hydrophobic cavity allows the encapsulation of low-molecular-weight organic molecules. Thus, cyclodextrin is a promising compound for removing micropollutant molecules from water. The binding mechanism of ligand molecules to the cavity of the cyclodextrin is driven by the physicochemical properties of the ligand such as its hydrophilic/hydrophobic balance and by its number of hydrogen bond donors and acceptors. In the present study, the free binding energies of nine different organic micropollutant molecules (bisphenol A, the charged and the uncharged forms of trimethoprim, the predominant forms of tetracycline at pH 1, pH 4, and pH 8, caffeine, theobromine, and atenolol) to β-cyclodextrin are calculated by molecular dynamics simulations using steered molecular dynamics and umbrella sampling analysis. Steered molecular dynamics and umbrella sampling analysis are shown to yield similar values for the free binding energy of the complexes, close to the experimental values. Then, the contributions of the electrostatics and van der Waals interactions to the free binding energy of the complexes are investigated, highlighting the major impact of van der Waals interactions. Finally, the effect of the number of hydrogen bonds between β-cyclodextrin and ligand molecules on their free binding energy is shown to depend on the octanol/water partition coefficients, log D, of the ligands. In particular, a correlation between the number of hydrogen bonds and the free binding energy of the complexes is demonstrated in the case of ligand molecules with log D values comprised in the range -0.55 - 0.92.
Keywords: 3402 Inorganic Chemistry; 3403 Macromolecular and Materials Chemistry; 34 Chemical Sciences; 3406 Physical Chemistry; 3407 Theoretical and Computational Chemistry; Chemical Physics; Binding energy; Ligands; Macrocyclic compounds; Molecules; Oligosaccharides